Effect of Molecular Structure on Interfacial Electron Transfer Kinetics in the Framework of Classical Marcus Theory. Issue 5 (7th October 2021) - Cho, Inseong; Mozer, Attila J.
Abstract: The factors affecting electron transfer at semiconductor electrodes sensitised with molecules and in contact with redox electrolytes have been studied for decades. Here, the influence of molecular structural factors enhancing or slowing down electron transfer rates at dye‐sensitised electrode interfaces are analysed by Marcus theory. Back electron transfer between TiO2 electrons and oxidised redox mediators are slowed down by reducing electronic coupling using alkyl chains or by minimising attractive intermolecular forces. Electron transfer between surface‐bound molecules and the electron donors, while generally also slowed down by alkyl chains, can also be enhanced by alkyl‐alkyl interactions. This review highlights the a priori difficult to predict effect of changing molecular structures on electron transfer. Systematic studies employing electron transfer measurements with fast time resolutions is needed to advance knowledge in this important area. Abstract :